PENERAPAN PERMAINAN DOMINO SEBAGAI UPAYA PENINGKATAN PRESTASI BELAJAR IPA SISWA KELAS VI DI SDN 4 KURANJI KOTA MATARAM - JAFAR ABDULLAH (Universitas Mahasaraswati Mataram, 2018)
All this time writer do science learning by using group discussion method and assignment. However, based on the analysis of the achievement of competence on students' understanding, especially on the material of plant breeding, students achievement is still low. This is indicated by the low test value on breeding. The author improves the way of learning to improve student learning achievement about breeding by implementing procedures and the use of learning media that is not boring, in the form of domino cards. The domino game is one of the strategies that can make students happy to learn by applying the principle: